2014
DOI: 10.1186/1756-0500-7-399
|View full text |Cite
|
Sign up to set email alerts
|

Triple negative breast cancer in a poor resource setting in North-Western Tanzania: a preliminary study of 52 patients

Abstract: BackgroundBreast cancer is the second leading cancer worldwide. In Tanzania, though it ranks as the second leading cancer in women after cervical cancer, hormonal receptor status is not carried out routinely in patients. Adjuvant hormonal therapy is given without prior knowledge of hormonal receptors status and patients can incur unnecessary costs and side effects. This study was performed to investigate the expression of hormonal receptors, epidermal growth factor receptors (HER-2) and proliferation index of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 25 publications
7
16
0
Order By: Relevance
“…This is similar to the reports in most of the African countries that reported aggressive BC to be high among young patients [15,19]. For example, in Uganda, Kenya and Tanzania it was reported that, most patients with BC were aged 50 years or younger and most of them 67.4%, 41.1% and 76.9%, respectively had tumour grade 3 [11,13,15]. However, these ndings differ from results of studies conducted in developed countries.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This is similar to the reports in most of the African countries that reported aggressive BC to be high among young patients [15,19]. For example, in Uganda, Kenya and Tanzania it was reported that, most patients with BC were aged 50 years or younger and most of them 67.4%, 41.1% and 76.9%, respectively had tumour grade 3 [11,13,15]. However, these ndings differ from results of studies conducted in developed countries.…”
Section: Discussionsupporting
confidence: 84%
“…Also Purdie et al reported that, ER-positive BC cases are more likely to be HER2-positive than PR-negative BC cases [29]. The expression of HER of 18.4% in the present study was similar to 18.5% which was reported in Brazil and lower than 40.7%, 24%, 23.1% and 22% that were reported in India, Ghana, Tanzania and Uganda [11,15,17,28]. Studies have shown that, expression of HER in both African American and African patients with BC is higher compared to Caucasians.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Hormonal therapy is another modality of breast cancer care. It is offered to patients with hormone receptor (ER and or PR) positive tumor [28,29]. There are various hormonal agents, and a single agent is usually given for a protracted period of about five years or more unless there is disease progression or relapse, and then they are switched to another [30,31].…”
Section: Resultsmentioning
confidence: 99%